Biopsychosocial impacts of alcohol abuse: Integrative review - Ribeiro, Aline Souto; Binato, Beatriz Majella; de Paula, Danielle Galdino; Ribeiro, Raisa Duarte da Silva (Seven Editora, 2024)
Based on the premise that alcohol use is a complex, multifactorial issue of great relevance to society, it is understood that there is no simple and universal answer that can account for all the problems involved in drug use and arising from it. To identify and analyze biopsychosocial factors in alcohol users, an integrative review was carried out based on articles available in the VHL online search portals, being listed: PubMed and Scielo. The initial search identified 202 publications on the subject, and 18 articles that met the objectives of the study were listed, based on the inclusion criteria. The lexical analyses, carried out with the Iramuteq® program, highlighted the proximity between words and classes, evidencing a significant distribution in the textual corpus, revealing two groups: Group 1: Biopsychosocial factors and alcohol consumption: behaviors associated with gender and age group and; Group 2: Early alcohol consumption: early approach x long-term consequences. The reviewed studies demonstrate a greater association with risk behavior and psychological disorders in women who use alcohol and; abusive consumption of alcohol experienced by children and adolescents, with this problem having a direct relationship with culture and social context. DOI:https://doi.org/10.56238/sevened2024.018-018